Prezi in EFL Classrooms: Reading Comprehension Outcomes and Student Perceptions in Indonesian Junior High School - Wanda Wahyuna; Ahmad Junaedi; Fajriani Fajriani; Reski Reski; Asdar Asdar (Universitas Sulawesi Barat, 2026)
Reading comprehension remains a persistent challenge in Indonesian EFL classrooms, where conventional instruction frequently fails to sustain meaningful student engagement with written texts. This study examined the effectiveness of Prezi, a web-based, zoomable presentation platform, as a digital teaching medium for improving eighth-grade students' reading comprehension, and explored student perceptions toward its use. A quasi-experimental design with a non-equivalent control group was employed, involving 48 students from two intact classes at SMP Negeri Mapilli, West Sulawesi, assigned to either Prezi-based instruction or conventional teaching across four treatment sessions. Data were collected through pre- and post-tests measuring literal, inferential, and critical reading comprehension, and a validated 14-item Likert-scale perception questionnaire. An independent sample t-test revealed a statistically significant between-group difference (t(46) = 6.311, p = .000), with the experimental group achieving a mean post-test score of 75.83 compared to 57.71 in the control group. The N-Gain score of 60.66% indicated sufficiently effective learning gains attributable to Prezi-based instruction. Student perceptions were strongly positive, yielding an overall score of 81.07%, classified as Very Successful. These findings suggest that Prezi holds meaningful pedagogical value as an engaging multimodal medium for EFL reading instruction in Indonesian junior high school contexts.